Perancangan Generator Induksi Magnet Permanen Kecepatan Rendah 12 Kutub Untuk Aplikasi Pembangkit Terbarukan - Sholihin, Sahid; , Agus Supardi, S.T., M.T (2016)
Electrical energy crisis that occurred in Indonesia is still an unresolved issues. From the problems related to research conducted electrical energy that can later be applied in remote areas by utilizing renewable energy sources as a driving source. This study discusses the design of a permanent magnet induction generator by utilizing an induction motor. Generator rotor design is done by implanting 12 pairs of permanent magnet type neodymium with dimensions of 35 x 15 x 7 mm. The design of the generator stator by changing the stator frame of 48 slots to 12 poles with winding numbered 4080. In this research, the testing generator with no load and load conditions. Testing without a load carried by the condition of the generator without the capacitor, the capacitor using a fixed size and change the size of the capacitor. Load testing is done by the variation in the form of a resistive load and inductive load. Permanent magnet induction generator with no-loads is able to generate voltages up to 75 to 130,7 volts and frequency 31.3 up to 53.8 Hz when rotated at speeds of 300 to 500 rpm without using capacitors. When retested by changing capacitor size from 4 μF to 12 μF is resulted 151.1 to 237.1 volts voltage and frequency 50.3 to 50.9 Hz with fixed rotational speed of 500 rpm. Furthermore, next experiment in no-loads condition with 10 μF Capacitors still generate a voltage 88 to 221 volts and frequency 30.3 to 50.8 Hz with a rotational speed of 300 to 500 rpm. Based on the test results proved that the capacitor acts as the excitation of voltage generation process. When the resistive load between 10 to 50 watts resulting voltage generator decreased from 202 to 141 volts and the current rise of 0.06 to 0.22 amperes, whereas the inductive load in the form of fluorescent lamp 10 to 40 watts resulting voltage generator decreased from 208 to 159.7 volts and current rise 0.20 to 0.34 amperes . The improvement of power load causes a decrease in the voltage and currrent rise.